Cold barrel zero - Quirk, Matthew (Mulholland Books/Little, Brown and Company, 2016)
John Byrne, a retired army doctor, has been working in the overnight ER of a Washington D.C. hospital, trying to outrun his past. This past includes service in a disgraced Special Ops Command Squad accused of committing an atrocious massacre. Thomas Hayes, the squad's leader who has been in hiding, reaches out to Byrne to enlist his help with a series of heists that will either prove their innocence - or culminate in a catastrophic terrorist attack.